2022
DOI: 10.1080/21655979.2022.2054205
|View full text |Cite
|
Sign up to set email alerts
|

Terpinen-4-ol inhibits the proliferation and mobility of pancreatic cancer cells by downregulating Rho-associated coiled-coil containing protein kinase 2

Abstract: Terpinen-4-ol (T4O), a compound isolated from the seeds of turmeric, has exhibited anti-malignancy, anti-aging, and anti-inflammatory properties in previous studies. However, the specific effects and molecular mechanisms of T4O on pancreatic cancer (PC) cells remain largely unknown. In this study, we demonstrated that T4O markedly suppressed PC cell proliferation and colony formation in vitro and induced apoptosis. Similarly, T4O significantly inhibited the migration and invasion of PC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…RNA sequencing further identified Rho-associated coiled-coil-containing protein kinase 2 (ROCK2) as the potential target of T-4-ol as it lowers its cellular levels in AsPC-1 and PANC-1 cells. These results were also validated in a subcutaneous tumorigenic model (BALB/c nude mice) where intraperitoneal injection of T-4-ol (40 mg/kg body weight, every 5 days) lowered tumor growth/progression and size accompanied by decreased expression of ROCK2 and epithelial-mesenchymal transition markers (PCNA, Ki-67, N-cadherin, and vimentin) [78]. In the subsequent study, Cao et al showed that the proliferation of LN229, T98, and U251 glioma cell lines is adversely affected by T-4-ol (1-4 μM) treatment [79].…”
Section: Anti-cancer Activity Of T-4-ol: Combating a Devastating Diseasementioning
confidence: 60%
See 1 more Smart Citation
“…RNA sequencing further identified Rho-associated coiled-coil-containing protein kinase 2 (ROCK2) as the potential target of T-4-ol as it lowers its cellular levels in AsPC-1 and PANC-1 cells. These results were also validated in a subcutaneous tumorigenic model (BALB/c nude mice) where intraperitoneal injection of T-4-ol (40 mg/kg body weight, every 5 days) lowered tumor growth/progression and size accompanied by decreased expression of ROCK2 and epithelial-mesenchymal transition markers (PCNA, Ki-67, N-cadherin, and vimentin) [78]. In the subsequent study, Cao et al showed that the proliferation of LN229, T98, and U251 glioma cell lines is adversely affected by T-4-ol (1-4 μM) treatment [79].…”
Section: Anti-cancer Activity Of T-4-ol: Combating a Devastating Diseasementioning
confidence: 60%
“…Recent investigations led by Cao and colleagues have also indicated the wide-spectrum anti-cancer potential of T-4-ol in effectively curtailing pancreatic cancer [78] and glioma [79]. The authors reported that T-4-ol (1-4 μM) significantly inhibited cellular proliferation, lowered cell migration and invasion (malignant phenotype) of AsPC-1 and PANC-1 pancreatic cell lines in vitro along with inducing apoptosis through increased caspase 3 cleavage and reduced Bcl-2 protein levels [78]. RNA sequencing further identified Rho-associated coiled-coil-containing protein kinase 2 (ROCK2) as the potential target of T-4-ol as it lowers its cellular levels in AsPC-1 and PANC-1 cells.…”
Section: Anti-cancer Activity Of T-4-ol: Combating a Devastating Diseasementioning
confidence: 99%
“…After high-quality clean reads were obtained and batch normalization was performed, the count data were analyzed using the EdgeR package. P values < 0.05 and |LogFold-Change| values ≥2 were used as test criteria for differentially expressed genes [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Medicinal plants are a huge source for drug discovery, and numerous studies have shown that plant extracts have anti-proliferative or anti-tumor effects on tumor cells [ 5 ]. Terpinen-4-ol (T4O) has anti-tumor, anti-bacterial, anti-fungal, anti-platelet, anti-oxidation, anti-senile dementia, and anti-metabolic syndrome properties [ 6 ]. Ken et al reported that T4O inhibits colorectal cancer growth by increasing the levels of reactive oxygen species [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ken et al reported that T4O inhibits colorectal cancer growth by increasing the levels of reactive oxygen species [ 7 ]. Furthermore, Cao et al have shown that terpine-4-ol inhibits the proliferation of pancreatic cancer cells by downregulating the Rho-associated coiled-coil protein kinase 2 [ 6 ]. However, the effects of T4O and its underlying mechanisms on gliomas have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%